Tempos sombrios, ecos de liberdade a palavra de Jean-Paul Sartre sob as imagens de Fernando Peixoto : no palco, Mortos sem sepultura (Brasil, 1977) - Cardoso, Maria Abadia (2007)
The scope of this research is a study on the Jean-Paul Sartre s play Death without burial, written in 1946 and staged in Brazil in 1977, under the guidance of director Fernando Peixoto. Regarding the subject matter description, at first one highlights its structure, placed in two different times: France in the 1940s, in the context of the German invasion and the French resistance, Brazil in the 1970s in the context of the military dictatorship and democratic resistance. One verifies that between drama literatures (the play writing) and staging there is a distance of space and time. As a result, themes, contends, agents, and intervention proposals gain new nuances. This reflection focuses on the study of the scene, resulting from a previous work where choices, artistic, intellectual investments, displacements, and propositions are made. In other words, the form and content of Sartre s construction are reread, inquired, and (re)appropriated by the stage setting. The first chapter treats of the play creative process, by investigating the way in which the dramatic structure and creation of the characters were made and legitimated. For that, an association between philosophy and dramaturgy was crucial to the understanding of the play writing. The second chapter deals, in the intellectual field, with the playwright s and director s reflections, circumscribed to distinct thought systems: the former is linked to the Existentialism; the latter, to the Marxist conception of left-wing. The third chapter focuses on the play stage setting in the midst of form, content, cutout work, changes, and adaptations matters. In the light of the temporality in which the scene is organized, the fourth chapter discusses the readings and debates roused by the drama criticism indicative of some questionings, for they refer to the formal answer to the drama text and establish a dialog with its social, historical universe.